Efficacy of intra-arterial chemotherapy with sequential anti-PD-1 antibody in unresectable gastric cancer: A retrospective real-world study - Xiang, Xiaosong; Guo, Feilong; Li, Guoli; Ma, Long; Zhu, Xi; Abdulla, Zulpikar; Li, Jiafei; Zhang, Junling; Huang, Mengli (Frontiers in Oncology, 2023)
Background: The prognosis of unresectable gastric cancer is poor, while the efficacy of anti-PD antibodies in conversion therapy has not been evaluated. Methods: Patients with unresectable gastric cancer who received intra-arterial chemotherapy (IAC) sequential anti-PD-1 antibody as induction therapy in Jinling Hospital were retrospectively analyzed. The primary outcome is R0 resection rate. The secondary outcomes include safety, conversion surgery rate, overall survival (OS) and progression free survival (PFS). Meanwhile, Tumor immunity in the microenvironment (TIME) before and after IAC was comprehensively dissected with multiplex immunofluorescence in order to detect possible mechanisms favoring anti-PD-1 treatment response. Results: Between May 2019 and October 2020, 36 patients received at least one cycle of IAC sequential anti-PD-1 antibody in our institution. The objective response was achieved in 28 patients (77.8%). Thirty patients (83.3%) successfully underwent conversion surgery, among which R0 resection was managed in 25/30 patients, and 23.3% (7/30) was assessed as pathological complete remission. During the median follow-up period of 19.7 months, patients who underwent R0 resection displayed superior OS (HR 0.14 [95% CI 0.04-0.50], P < 0.0001) and PFS (HR 0.11 [0.03-0.44], P < 0.0001) than those who did not. Grade 3 adverse events (AEs) were only encountered in 19.4% patients, no grade 4 AEs observed. In TIME analysis, the number of tertiary lymphoid structures (TLSs) (P = 0.004) were greatly induced by IAC, as well as CD8+ T cells (P = 0.011) and PD-1+ cells (P = 0.025). Meanwhile, Tumor associated macrophages shifted towards anti-tumor M1-like subtypes, with CD68+CD163+ M2-like subpopulation significantly decreased (P = 0.04). Conclusion: IAC sequential anti-PD-1 antibody exhibited promising clinical benefit for unresectable gastric cancer with remarkable conversion rate and R0 resection rate. TIME transformation induced by ICA might mediate the additive effect with the immune checkpoint inhibitor.